Descriptions of Disordered Eating in German Psychiatric Textbooks, 1803–2017 - Bergner, Lukas; Himmerich, Hubertus; Kirkby, Kenneth C.; Steinberg, Holger (Frontiers in Psychiatry, 2021)
The most common eating disorders (EDs) according to DSM-5 are anorexia nervosa (AN), bulimia nervosa (BN) and binge eating disorder (BED). These disorders have received increasing attention in psychiatry due to rising prevalence and high morbidity and mortality. The diagnostic category “anorexia nervosa”, introduced by Ernest-Charles Lasègue and William Gull in 1873, first appears a century later in a German textbook of psychiatry, authored by Gerd Huber in 1974. However, disordered eating behavior has been described and discussed in German psychiatric textbooks throughout the past 200 years. We reviewed content regarding eating disorder diagnoses but also descriptions of disordered eating behavior in general. As material, we carefully selected eighteen German-language textbooks of psychiatry across the period 1803-2017. Previously, in German psychiatry, disordered eating behaviors were seen as symptoms of depressive disorders, bipolar disorder or schizophrenia, or as manifestations of historical diagnoses no longer used by the majority of psychiatrists such as neurasthenia, hypochondria and hysteria. Interestingly, 19th and early 20th century psychiatrists like Kraepelin, Bumke, Hoff, Bleuler, and Jaspers reported symptom clusters such as food refusal and vomiting under these outdated diagnostic categories, whereas nowadays they are listed as core criteria for specific eating disorder subtypes. A wide range of medical conditions such as endocrinopathies, intestinal or brain lesions were also cited as causes of abnormal food intake and body weight. An additional consideration in the delayed adoption of eating disorder diagnoses in German psychiatry is that people with EDs are commonly treated in the specialty discipline of psychosomatic medicine, introduced in Germany after World War II, rather than in psychiatry. Viewed from today’s perspective, the classification of disorders associated with disordered eating is continuously evolving. Major depressive disorder, schizophrenia and physical diseases have been enduringly associated with abnormal eating behavior and are listed as important differential diagnoses of EDs in DSM-5. Moreover, there are overlaps regarding the neurobiological basis and psychological and psychopharmacological therapies applied to all of these disorders.